Supporting Carbon Tax Implementation in Developing Countries through Results-Based Payments for Emissions Reductions - Strand, Jon (World Bank, Washington, DC, 2020)
This paper discusses compensation mechanisms to strengthen incentives for lower-income countries to adopt carbon taxes through donor-funded support programs. The paper considers two cases: the provision of climate finance when the host country uses the additional mitigation to meet its own greenhouse gas mitigation target (the "incremental cost price"); and a transaction in an international carbon market with the mitigation credit created by host country mitigation transferred outside the country (the “opportunity cost price”). Both offset the host country's deadweight loss from imposing a carbon tax, which is lower when the host country enjoys large co-benefits from mitigation. Formulas are derived for the incremental cost price and the opportunity cost price. The opportunity cost price is always larger than the incremental cost price, as the host country under the opportunity cost price must use additional, more expensive mitigation policies to reach its mitigation target. The paper discusses additional costs and barriers that deter hosts from adopting carbon taxes. These arguments can help to explain why few low-income countries have so far adopted carbon taxes, and why the necessary compensation for tax adoption may exceed theoretical assessments.